(untitled) (Limes: Revista de Estudios Clásicos, 2023)
The first part of the present article (§1-3) aims to track down the function of the improper descripti (or apographs) in Paul Maas’ Textkritik. These witnesses can be defined as those whose ancestor is lost, unlike proper descripti (whose ancestor is preserved), but which nevertheless are useless to reconstruct said ancestor and, therefore, need not be taken into account for the constitutio textus. The second part will test the usefulness of this distinction between proper and improper descripti, applying it to a series of stemmata presented by M. Reeve. It will conclude that Maas’ method is synchronic rather than diachronic.